How virtual reality affects consumer choice - Meißner, Martin; Pfeiffer, Jella; Peukert, Christian; Dietrich, Holger; Pfeiffer, Thies (Journal of business research, 2020)
With high-immersive virtual reality (VR) systems approaching mass markets, companies are seeking to better understand how consumers behave when shopping in VR. A key feature of high-immersive VR environments is that they can create a strong illusion of reality to the senses, which could substantially change consumer choice behavior compared to online shopping. We compare consumer choice from virtual shelves in two environments: (i) a high-immersive VR environment using a head-mounted display and hand-held controllers with (ii) a low-immersive environment showing products as rotatable 3-D models on a desktop computer screen. We use an incentive-aligned choice experiment to investigate how immersion affects consumer choice. Our investigation comprises three key choice characteristics: variety-seeking, price-sensitivity, and satisfaction with the choice made. The empirical results provide evidence that consumers in high-immersive VR choose a larger variety of products and are less price-sensitive. Choice satisfaction, however, did not increase in high-immersive VR.